Maleated hydroxyethyl cellulose for the efficient removal of Cd(II) ions from an aqueous solution: isothermal, kinetic and regeneration studies - Khan, Fatima; Siddique, Abu Bakar; Irfan, Muhammad Imran; Hassan, Muhammad Naeem ul; Sher, Muhammad; Alhazmi, Hassan A.; Qramish, Abdulrahman N.; Amin, Hatem M. A.; Qadir, Rahman; Abbas, Azhar (Springer Nature, 2024)
The massive environmental pollution caused by widespread industrialization jeopardizes human life and ecosystems. Among several pollutants, heavy metal ions in fresh water reservoirs pose a major threat that needs an immediate attention. One of the feasible, cheap and robust approaches to mitigate this pollution is the sorption on efficient and easily available materials. Hence, the contemporary study is designed to the synthesis, characterization, and application of the sodic form of hydroxyethyl cellulose maleate (HEC-MAL-Na) for the selective uptake of Cd(II) metal ions from the spiked aqueous solution. The esterification of hydroxyethyl cellulose (HEC) with maleic anhydride was initially carried out to synthesize HEC-MAL. HEC-MAL was subsequently neutralized by NaHCO3 to form HEC-MAL-Na. The sodic form of HEC-MAL was characterized by comparing the FT-IR spectra of HEC-MAL-Na, HEC-MAL and HEC. Zero-point charge pH of HEC-MAL-Na confirmed the neutralization of HEC-MAL by NaHCO3. HEC-MAL-Na was utilized as an adsorbent for the treatment of polluted water by removing Cd(II) ions via an ion-exchange mechanism. The optimum conditions for the effective removal of Cd(II) ions from the aqueous solution were determined by screening different parameters such as temperature, pH, contact time, sorbent dose and initial metal ion concentration. The experimental data supported the pseudo-second order kinetics and Langmuir isothermal model for removal of Cd(II) ions from aqueous solution with the maximum sorption capacity of 277.7 mg/g at pH 5.5, initial metal ion concentration (110 mg L−1), sorbent dosage (40 mg) and contact time (30 min) at 298 K. The thermodynamic parameters, such as ∆S°, ∆H° and ∆G° were also estimated, and their values indicated the exothermic, spontaneous and feasible nature of the sorption process. Regeneration studies demonstrated the feasibility of the repeated use of activated adsorbent for removal of heavy metal ions.